การเก็บกลับคืนสังกะสีจากฝุ่นเตาหลอมอาร์คไฟฟ้าโดยวิธีการชะละลายด้วยกรดซัลฟิวริกเจือจาง - วิสารัช มั่นประพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Electric arc furnace dust (EAFD) containing iron, zinc, and lead are generated. The largest metallic portion of EAFD is zinc, which varies between 24-27%. Zinc in EAFD mainly presents as franklinite (ZnFe₂O₄) and zincite (ZnO). Zinc ferrite (franklinite) is considerably refractory against leaching. In this research, the EAFD characterization and its leaching process by thermal treatment and dilute sulphuric acid (H₂SO₄) are performed. The leaching process was based on the zinc extraction with dilute sulphuric acid from EAFD under atmospheric conditions, without any using preliminary treatment and using thermal treatment by roasting with salts (NaCl) to increase dissolution of refractory zinc. Statistical design and analysis of experiments is carried out to determine the main effects of the leaching process factors, with acid normality, shaking time and solid to liquid ratio. Zinc was extracted by using an EAFD. Sulfuric acid was used at different concentrations to recover zinc from dust particles. The highest zinc extraction was obtained at low acid concentration 1 mol/L. The kinetics of zinc extraction showed a maximum zinc recovery of 92%